Cultural Terms and Their Translation in A Thousand Splendid Suns Novel - Wahyudi , I Wayan Agus Tira; Jayantini , I Gusti Agung Sri Rwa; Winarta , Ida Bagus Gde Nova (Institut Pariwisata dan Bisnis Internasional, 2023)
The study concerns on the translation of cultural terms in A Thousand Splendid Suns novel. It aims analyzing the types of cultural terms and translation technique found in A Thousand Splendid Suns novel. This qualitative research was done through a descriptive analysis based on Newmark’s theory and Molina and Albir theory to analyze the data. It was found that there are five categories cultural terms in this data that are social organization which has forty seven (47) data or 48,959%. Then, it followed by the material culture which has thirty two (32) data or 33,333%. The other that is ecological has eleven (11) data or 11,458%. The lowest were social culture which has three (3) data or 3,125% and gestures and habits has three (3) data or 3,125%. It can be concluded that social organization is the highest occurrence of the data the translation of cultural terms found in A Thousand Splendid Suns novel.